Polypoid pulmonary arteriovenous malformation causing hemothorax treated with thoracoscopic wedge resection - Haruhiko Shiiya; Yasuhiro Suzuki; Shigeo Yamazaki; Kichizo Kaga (Surgical Case Reports)
Abstract Background Pulmonary arteriovenous malformations (PAVMs) can be associated with life-threatening complications such as paradoxical embolization, cerebral abscess, and hemothorax. Therefore, all adults with PAVMs should be offered treatment. Percutaneous transcatheter embolization is the first-line treatment, but 5–25% of cases require further treatment due to persistence after embolization. Recently, the role of minimally invasive thoracic surgery as a definitive treatment has been evaluated. We describe a case of a small peripheral PAVM causing hemothorax, which was safely treated with video-assisted thoracoscopic surgery (VATS). In our case, the PAVM appeared to protrude into the pleural cavity on chest computed tomography (CT), perhaps explaining why it led to a hemothorax. Case presentation A 64-year-old man with a history of a brain abscess, for which he underwent surgery 6 months previously, developed a left-sided hemothorax. He had experienced recurrent epistaxis and received anticoagulation therapy for chronic atrial fibrillation. Chest CT after drainage revealed a solitary 15-mm nodule in the periphery of the left lower lobe, and identification of a feeding artery and draining vein on three-dimensional CT suggested that the node was a PAVM. The PAVM was adjacent to the diaphragm and multi-detector CT (MDCT) and three-dimensional CT (3DCT) showed that the nodule slightly displaced the diaphragm and protruded into the pleural cavity. After discussion in a multidisciplinary conference, it was decided that surgical treatment would be preferable to catheter embolization. The patient underwent VATS with three ports, the largest of which was 15 mm. The PAVM protruded from the peripheral lung like a polyp, and wedge resection was performed after simple adhesiolysis. There were no complications, and the patient is asymptomatic after 1-year of follow-up. Conclusions As in the present case, PAVMs protruding into the pleural cavity can cause hemothorax, and surgical wedge resection of the involved lung as a definitive treatment is feasible and possibly safer than catheter embolization, particularly if the PAVM is localized close to the visceral pleura. Protrusion into the pleural cavity (polypoid appearance) was detected using MDCT and 3DCT preoperatively.